Descriptive Study of Respirable Dust Levels By Furniture Industry Workers in Nanggalo District, Padang City in 2020 - Darwel Darwel; Fini Alvionita; Alsri Windra Doni; Denos Imam Fratama (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2022)
Rapid development, especially in the field of industry and technology, causes changes in the composition of the air beyond the carrying capacity of the environment, this has a negative impact on humans, namely air pollution and pollution that can affect the degree of human health, especially the furniture industry in Padang City, precisely in Nanggalo District. This study aims to determine the levels of inhaled dust (Respirable) by workers in the furniture industry in Nanggalo District. The design of this research is descriptive, which describes the levels of inhaled dust (Respirable) by furniture industry workers in Nangalo District, Padang City in 2020. The population in this study was 48 workers, a sample of 21 workers was taken based on the number of workers in the furniture industry who worked in the production section. The data obtained were analyzed univariately. The results of the study using the Personal Dust Sampler tool used for each worker showed that the levels of inhaled dust (Resprable) by 15 furniture industry workers in Nanggalo District were found to meet the requirements, namely < 3 mg/m3 and 6 workers did not meet the requirements, namely > 3 mg/m3. It can be concluded that the levels of dust inhaled by furniture industry workers in Nanggalo District are those who meet the requirements and some do not. It is recommended for companies or the management of the furniture industry in Nanggalo District, namely providing and supervising the use of personal protective equipment (PPE) for workers, and the need for renovation of production sites, especially the provision of insulation and arrangement of safe and comfortable work spaces between workers.